Financial Performance Analysis of Local Government Financial Management in Jambi City During 2011–2024 - Semintariah Ginting; Zulgani; Rahma Nurjanah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to analyze the development of regional financial performance and evaluate the financial performance of the Jambi City Government based on four key ratios: the regional financial independence ratio, the degree of fiscal decentralization ratio, the effectiveness ratio of locally generated revenue (PAD), and the regional financial efficiency ratio during the 2011–2024 period. The research employs a descriptive quantitative approach using secondary data sourced from BPKAD the Jambi City Regional Budget (APBD) realization reports. The results show that the development of Jambi City’s regional finances experienced nominal growth, with PAD increasing by 6.23 percent and regional expenditures by 6.24 percent. However, in terms of quality, the region’s financial capacity remains in the low category due to its high dependence on central government transfer funds. In terms of financial performance, the effectiveness ratio of PAD is categorized as very effective in most years. However, the financial efficiency ratio remains in the less efficient category. Meanwhile, the financial independence ratio and the fiscal decentralization ratio indicate that PAD’s contribution to total revenue is still limited, reflecting the low level of fiscal independence in Jambi City. This research suggests the need for policies aimed at strengthening regional fiscal capacity, optimizing PAD collection, and improving the efficiency of regional spending.